Evaluation of primary health workers training program to provide psychoeducation to family caregivers of persons with psychotic disorder - Carla Raymondalexas Marchira; Warih Andan Puspitasari; Ida Rochmawati; Siti Mulyani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABTRACT Many persons suffering psychotic illnesses, such as schizophrenia, are largely untreated in low income countries. In these settings, most persons with severe mental illness live with their families. Thus, families play a particular critical role in determining whether a person with a psychotic illness will receive treatment and what the quality of treatment. Psychoeducation has proven to be extremely effective in helping families develop the knowledge and skills which is necessary to help their family members. Indonesia has a national policy to integrate the management of mental health problems into the primary health care system. However, in practice, such care does not implemented effectively. A preliminary study in primary health centers in two districts of Bantul and Gunung Kidul regency, Yogyakarta province, showed that there was very little or there is not any training for health care workers on diagnosis and treatment of psychotic disorder. This study was conducted to evaluate the effectiveness of the training program for health workers in three primary health centers in Yogyakarta, Indonesia, to provide psychoeducation to family caregivers for persons with psychotic disorder. A quasi-experimental study with the approach of one group pre and posttest design was performed in this study. Fortythree health workers in 3 primary health centers in Bantul and Gunung Kidul, Yogyakarta were trained every week for a month to provide psychoeducation to family caregivers who live with psychotic disorder patient. Result showed that the baseline score of knowledge of schizophrenia among health workers in 3 primary health centers in Bantul and Gunung Kidul before training were not significantly different (p=0.162). After the psychoeducation training program there were significantly different (p=0.003) of the score of knowledge of schizophrenia among health workers in 3 primary health care centers compared with before training. For conclusion, the training program to provide psychoeducation to family care providers of persons with psychotic disorder for primary health workers was effective to increase their knowledge of schizophrenia.